Digitization of public services in the Czech Republic and Ukraine - Ialinskaia, Elizaveta (2023)
The presented master thesis focuses on the digitization of public administration services in the Czech Republic and Ukraine, with a comparative analysis between these two countries. The aim is to assess the current state of digitized public services in these countries by collecting and analyzing data from official governmental sources, conducting a comparative analysis, and analyzing the gaps in the digitization process of public administration services in both countries. The study aims to facilitate the exchange of knowledge and experiences between these countries, with the goal of enhancing the digitization of public administration services and fostering their development. Based on the findings, a set of recommendations will be proposed to scale up the digitization of public administration services in the Czech Republic and Ukraine.